The Arab intellectual between the witnessed and the desired, according to Hisham Sharabi - Said Karoui (Social Empowerment Journal, 2023)
Progress, progress, intellectual and cultural renaissance, and everything related to the establishment of culture, can only be achieved by addressing the cultural reality in general and the Arab one in particular. The cultural field is considered a vital field that must be studied, the obstacles that overwhelm it diagnosed, and solutions found, proposed and denounced in order to build a desired and stable reality.It has become obligatory to engage in permanent and continuous awareness of the cultural issue by paying attention to everything related to it. This modest article is considered a socio-cultural study of the thought of Hisham Sharabi (1927-2005 AD), who lived in a painful social and political context, and dealt with the roles of the Arab intellectual within the Arab reality, and dealt with his capabilities and tools through criticism and dismantling them, and calling for their renewal to keep pace with the requirements of the social class and activate it in Ground.